Jual Beli Harta Bersama Tanpa Persetujuan Istri Sah: Analisis Sanksi Hukum dalam Perspektif Teori Akibat Hukum - Hartawati, Yunita Maria Magdalena; Marniati, Felicitas Sri; Setiadi, Yuliana (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2025)
Property acquired during marriage constitutes joint property and may only be transferred with the consent of both husband and wife as regulated in Law Number 1 of 1974. However, in practice, there are still cases of land sales as joint property conducted before the Land Deed Official (PPAT) without the wife’s consent. This research aims to analyze the legal consequences and legal certainty of such sale and purchase deeds. This study employs normative legal research with statutory, conceptual, analytical, and case approaches. Legal materials are obtained from legislation, literature, and court decisions, and analyzed using interpretative and constructive techniques. The results indicate that a sale and purchase deed made without the wife’s consent has no legal effect, as it is null and void by court decision. Such cancellation ensures legal certainty and protects the wife as the aggrieved party. The implication is that PPAT practices must pay greater attention to the subjective requirements of agreements to ensure that transactions involving joint property comply with the law and avoid disputes.